Effect of the El Niño–Southern Oscillation (ENSO) Cycle on the Catches and Habitat Patterns of Three Swimming Crabs in the Taiwan Strait - Muhamad Naimullah; Yan-Lun Wu; Ming-An Lee; Kuo-Wei Lan (Frontiers in Marine Science, 2021)
The swimming crabs is a crucial predator species in benthic habitats and a high value in commercial fishery industries in subtropical and tropical Asia. The climate variability caused by El Niño–Southern Oscillation (ENSO) events has substantial impacts on the catch and habitat of this species. In this study, a weighted habitat suitability index (HSI) model was constructed using logbooks and voyage data records from Taiwanese crab vessels (2013–2019) with the addition of environmental variables to examine the influence of ENSO events on catch rates (CRs) and habitat suitability for Charybdis feriatus , Portunus pelagicus , and Portunus sanguinolentus in the Taiwan Strait (TS). The autumn (September–October) is the major fishing season for catching these three swimming crab species in the TS. A high CR of P. sanguinolentus was observed across the TS, whereas high CRs of P. pelagicus and C. feriatus were recorded in areas in the southern and northern TS, respectively, during autumn. Moreover, the CRs for C. feriatus and P. pelagicus were higher (>7.0 and >8.0 kg/h) during La Niña events, with the increase being more than 40.0% compared with the CRs under normal and El Niño events in autumn. For P. sanguinolentus , the CRs were higher during both La Niña and El Niño events (>8.0 kg/h) compared with normal years. The high CRs for C. feriatus and P. sanguinolentus during autumn in La Niña years co-occurred with high sea temperature and low salinity, whereas the high CR of P. pelagicus co-occurred with high sea temperature and high salinity. Furthermore, the high CRs for C. feriatus and P. pelagicus were observed in areas with high HSI in the La Niña years but were distributed more widely with a lower HSI during normal and El Niño years. The low CRs for C. feriatus and P. pelagicus during normal and El Niño years and the low CR for P. sanguinolentus in normal years during autumn were highly consistent with substantial shrinkage of suitable habitats. Our findings suggest that ENSO events strongly affected the catch and habitat suitability of C. feriatus , P. pelagicus , and P. sanguinolentus during autumn in the TS.